Structural Stability and Vibration An Integrated Introduction by Analytical and Numerical Methods - Wiggers, Sine Leergaard (Springer Tracts in Mechanical Engineering,, 2018)
This book offers an integrated introduction to the topic of stability and vibration. Strikingly, it describes stability as a function of boundary conditions and eigenfrequency as a function of both boundary conditions and column force. Based on a post graduate course held by the author at the University of Southern Denmark, it reports on fundamental formulas and makes uses of graphical representation to promote understanding. Thanks to the emphasis put on analytical methods and numerical results, the book is meant to make students and engineers familiar with all fundamental equations and their derivation, thus stimulating them to write interactive and dynamic programs to analyze instability and vibrational modes. .